Processes of change in cognitive behavioral therapy for treatment-resistant depression: psychological flexibility, rumination, avoidance, and emotional processing. (16th November 2020) - Yasinski, Carly; Hayes, Adele M.; Ready, C. Beth; Abel, Anna; Görg, Nora; Kuyken, Willem
Abstract: Recent clinical research suggests that facilitating psychological flexibility and emotional processing and decreasing rumination and avoidance are important tasks of treatment for disorders characterized by entrenched patterns of psychopathology, such as major depressive disorder. The current study examined these processes as predictors of treatment outcomes in a subsample of depressed adult patients ( n  = 49) who had not fully responded to antidepressant medication and were randomized to receive cognitive–behavioral therapy (CBT). Target variables were coded from session recordings at baseline and in the vicinity of two therapeutic transition points: a sudden gain (improvement) and a transient spike in depression symptoms, or at similar periods for those without such transitions. Results indicated that psychological flexibility during the pre-sudden gain period predicted less depression at 12-month follow-up, beyond baseline symptoms and other co-occurring processes. Interaction analyses revealed that when flexibility was low during the post-spike period, avoidance and rumination predicted higher depressive symptoms, whereas emotional processing predicted lower symptoms at the 12-month follow-up. When flexibility was high, none of these variables were associated with outcome. Together, these findings highlight psychological flexibility as a key therapeutic target in CBT for treatment-resistant depression and might have implications for relapse prevention.